Zagotavljanje kakovosti pri razvijanju mamogramov - Miklavčič, Lucijan (Radiology and oncology (Ljubljana), 1999)
The practice of using a sensitometer to evaluate the film processing consistency must be well known to those involved with quality control procedures for general radiology and especially for mammography. This paper introduces to the basic perfofmance parameters in monitoring mammographic filmprocessing.
Keywords: diagnostika; dojke; kvaliteta; Mammography; mamografija; Quality control; Technology, radiologic; X-ray film